Penerapan Kaidah Fiqih dalam Penetapan Hukum Islam Bedah Mayat Kedokteran - Husairi, Ahmad (Jurnal Berkala Kedokteran, 2014)
Abstract: The medical autopsy is a post-mortem that is performed for the benefit of the medical world. On the one hand, the corpse is the body that must be respected. On the other hand, the medical profession can not be separated from the implementation of the post-mortem. Therefore, the Islamic jurisprudence of post-mortem should be determined by careful consideration in order to obtain the best benefit. Since the Islamic jurisprudence of medical autopsy was not stated in the Quran and hadith, ijtihad method should be performed. The rules of Islamic jurisprudence is the rule that is reliable in addressing different issues of Islamic jurisprudence, including the issues of Islamic jurisprudence of medical autopsy. Thus, the rules of Islamic jurisprudence can be applied in consideration of determination of Islamic jurisprudence of medical autopsy. Keywords: autopsy, Islamic jurisprudence of autopsy, the rules of Islamic jurisprudenceÂ Abstrak: Bedah mayat kedokteran merupakan bedah mayat yang dilakukan untuk kepentingan dunia kedokteran. Di satu sisi, mayat merupakan jasad yang harus dihormati. Di sisi lain, profesi kedokteran tidak dapat terlepas dari pelaksanaan bedah mayat. Oleh karena itu, hukum Islam bedah mayat perlu ditetapkan dengan pertimbangan yang mendalam agar dapat diperoleh kemaslahatan yang terbaik. Berhubung hukum bedah mayat kedokteran tidak ada disebutkan dalam Al-qurâan dan hadits, metode ijtihad harus dilakukan. Kaidah fiqih merupakan kaidah yang cukup andal dalam menjawab berbagai masalah hukum Islam, termasuk masalah hukum bedah mayat kedokteran. Dengan demikian, kaidah fiqih dapat diterapkan dalam pertimbangan penetapan hukum Islam bedah mayat kedokteran.Â Kata kunci: Bedah mayat, hukum Islam bedah mayat, kaidah fiqih